Penatalaksanaan Pada Anak Perempuan Usia 12 Bulan Penderita Stunting dan Mikrosefali Disertai Pola Asuh Kurang Tepat Melalui Pendekatan Kedokteran Keluarga Di Wilayah Puskesmas Karang Anyar - Machmud Aminudin; Mayasari, Diana (Medula, 2025)
Stunting is a condition of short or very short stature based on body length/height according to age that is smaller than -2 Standard Deviation (SD) on the 2006 World Health Organization (WHO) growth curve. Whereas microcephaly is a small head circumference that is below -2 Standard Deviation (SD) based on the mean on gender and age. In this case there was an 11 month old female patient with body weight was: 5.7 kg (W/A: <-3SD); height: 60 cm (H/A: <-3SD); head circumference: 34 cm (HC/A: <-2SD); upper arm circumference: 11 cm with BMI: 15.8 kg/m2. Stunting and microcephaly are correlated in having a big impact on children's growth and development. Therefore, holistic management is needed with a family medicine approach including patient centered, family focused and community oriented to encourage improvements in the patient's condition and family behavior in order to improve the patient's quality of life. Purpose of mplementation of holistic and comprehensive family doctor services by identifying risk factors, clinical problems, and management of stunting and microcephaly patients based on Evidence Based Medicine through a patient centered care and family approach. This study is a case report using primary and secondary sources. Primary data was obtained through anemnesis (alloanamnesis), physical examination and home visits. Secondary data was obtained from the KIA posyandu book. Assessment based on a holistic diagnosis from the beginning, process and end of the study is carried out qualitatively and quantitatively. Key Words: Family Medicine, Microcephaly, Stunting